Proporcionalidade processual e precedentes : aplicações no processo coletivo e IRDR - Schneider, Stella Reis (2025)
The overburdening of the judicial system is a problem that directly impacts the conception of effective access to justice. Although the democratization of access is a constantly pursued goal, its guarantee also generates undesirable side effects such as system congestion, case repetition, and predatory litigation. Legal literature indicates that the adversarial culture is a contributory factor to the individualism entrenched in the Brazilian procedural model. In daily practice, the difficulty in embracing the cooperative model is observed, which, combined with mistrust regarding the use of collective and aggregative methods for case resolution, reduces the judge to a mere adjudicator of cases. Resistance to judicial decisions (access to higher courts through multiple appeals) and the repeated violation of rights by large litigants exacerbate the situation. Given this scenario, the research employs a discursive method based on dialectical data analysis of bibliographic and jurisprudential sources, proposing the use of the principle of procedural proportionality 3 the central idea 3 as a tool for case management. Drawing from the concept of the three-dimensionality of justice, the research identifies bases for tailoring procedures and efforts to the complexity of each case, determining the necessary resources and the reasonable time for problem resolution. The identified problem requires the judiciary to position itself as a problem-solver addressing the root causes of repetitive cases or recurrences, rather than merely adjudicating cases, which fails to resolve the overload and congestion. The importance of precedents, collective procedures, and the Incident of Resolution of Repetitive Demands (IRDR) is highlighted in the operation of a more efficient, rational, and just system. In the research, repetitiveness 3 as a symptom 3 is treated as a crucial element for adopting precedents, collective procedures, and the IRDR as case management techniques. By implementing the principle of procedural proportionality within the three-dimensional view of justice and establishing precedents, the study aims to demonstrate that collective procedures and the IRDR are effective solutions for promoting effective access to justice